PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN - Cornecia, Vinca; Setijaningsih, Herlin Tundjung (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This study aims to analyze the effect of profitability, firm size, and capital structure on firm value in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period. The sample selection used in this study used a purposive sampling method and the selected sample was 65 companies The Data processing technique uses multiple linear regression analysis and the data collected were processed using EViews 12.0 software. The results of this study indicate that profitability, firm size, and capital structure simultaneously have a significant effect on firm value. Then partially, profitability and capital structure have a positive and significant effect on firm value while firm size has a negative and significant effect on firm value.